PIP2: A critical regulator of vascular ion channels hiding in plain sight - Harraz, Osama F; Hill-Eubanks, David; Nelson, Mark T (Proceedings of the National Academy of Sciences - PNAS, 2020)
The phosphoinositide, phosphatidylinositol 4,5-bisphosphate (PIP2), has long been established as a major contributor to intracellular signaling, primarily by virtue of its role as a substrate for phospholipase C (PLC). Signaling by Gq-protein-coupled receptors triggers PLC-mediated hydrolysis of PIP2 into inositol 1,4,5-trisphosphate and diacylglycerol, which are well known to modulate vascular ion channel activity. Often overlooked, however, is the role PIP2 itself plays in this regulation. Although numerous reports have demonstrated that PIP2 is critical for ion channel regulation, how it impacts vascular function has received scant attention. In this review, we focus on PIP2 as a regulator of ion channels in smooth muscle cells and endothelial cells-the two major classes of vascular cells. We further address the concerted effects of such regulation on vascular function and blood flow control. We close with a consideration of current knowledge regarding disruption of PIP2 regulation of vascular ion channels in disease.The phosphoinositide, phosphatidylinositol 4,5-bisphosphate (PIP2), has long been established as a major contributor to intracellular signaling, primarily by virtue of its role as a substrate for phospholipase C (PLC). Signaling by Gq-protein-coupled receptors triggers PLC-mediated hydrolysis of PIP2 into inositol 1,4,5-trisphosphate and diacylglycerol, which are well known to modulate vascular ion channel activity. Often overlooked, however, is the role PIP2 itself plays in this regulation. Although numerous reports have demonstrated that PIP2 is critical for ion channel regulation, how it impacts vascular function has received scant attention. In this review, we focus on PIP2 as a regulator of ion channels in smooth muscle cells and endothelial cells-the two major classes of vascular cells. We further address the concerted effects of such regulation on vascular function and blood flow control. We close with a consideration of current knowledge regarding disruption of PIP2 regulation of vascular ion channels in disease.